The role of BDNF in the clinical course of primary headaches - Bahtigul Holmuratova; Nilufar Rashidova; Khanifa Khalimova; Rustam Matmurodov; Gulnora Rakhmatullaeva (SAGE Publishing, 2023)
Objective: Brain-derived neurotrophic factor (BDNF) is associated with the pathophysiology of primary headaches. The present study aimed to investigate interictal and ictal BDNF levels and its association with clinical parameters in patients with primary headaches. Methods: Three groups of headache patients enrolled in this study: patients with episodic migraine with and without aura, cluster headaches, and tension-type headaches according to the current criteria of the International Headache Society. In migraine patients and cluster headache patients, venous blood samples were collected twice: outside and during attacks. In patients with tension-type headaches and healthy controls, one single blood sample was taken. The research comprised 120 patients (males and females) suffering from primary headaches. The control group consisted of 30 healthy volunteers. Results: This is the first study to show that there is no gender difference BDNF levels in Uzbek patients with primary headaches. Migraine and cluster headache patients revealed significantly higher BDNF serum levels during headache attacks compared with attack-free periods ( p < 0.02). Conclusion: This reinforces the view that BDNF may be implicated in the pathophysiology of primary headaches.